Involvement of the Right Dorsolateral Prefrontal Cortex in Numerical Rule Induction: A Transcranial Direct Current Stimulation Study - Yao, Yuzhao; Jia, Xiuqin; Luo, Jun; Chen, Feiyan; Liang, Peipeng (Frontiers in Human Neuroscience, 2020)
Numerical inductive reasoning, the ability to extrapolate a general rule or relation from a set of specific numerical elements, has been considered as an integral component of many cognitive activities. Importantly, previous behavioral studies have consistently reported that one critical component of numerical inductive reasoning is checking, which often occurs when a discrepant element is discovered and reprocessing is needed to determine whether the discrepancy is an error of the original series. However, less is known about the neural mechanism underlying the checking process. Given that the checking effect involves cognitive control processes such as the conflict resolution that are linked to right DLPFC, this study hypothesizes that the right DLPFC may play a specific role in the checking process. To test our hypothesis, this study utilized the transcranial direct current stimulation (tDCS), a non-invasive brain stimulation method that could modulate cortical excitability, and examined whether and how the stimulation of the right DLPFC via tDCS could modulate the checking effect during a number-series completion problem task. Ninety healthy participants were allocated to one of the anodal, cathodal and sham groups and completed four sessions including button-press practice, number-series practice, stimulation on the right DLPFC and formal number-series task. Subjects were required to verify whether number sequences formed rule-based series, and checking effect was assessed by the difference in performance between invalid and valid conditions. The results showed that the anodal tDCS significantly facilitated the process of checking. This finding suggested that the right DLPFC may play a critical role in the checking process of numerical inductive reasoning.